2020
DOI: 10.1016/j.xcrm.2020.100122
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Approach to Restore a Slow-Oxidative Phenotype and Defective CaMKIIβ Signaling in Limb Girdle Muscular Dystrophy

Abstract: Summary Mutations in CAPN3 cause limb girdle muscular dystrophy R1 (LGMDR1, formerly LGMD2A) and lead to progressive and debilitating muscle wasting. Calpain 3 deficiency is associated with impaired CaMKIIβ signaling and blunted transcriptional programs that encode the slow-oxidative muscle phenotype. We conducted a high-throughput screen on a target of CaMKII ( Myl2 ) to identify compounds to override this signaling defect; 4 were tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…Interestingly, it has been recently shown that calcium dyshomeostasis may be an early phenomenon in this model ( DiFranco et al, 2016 ). In contrast to reports from C3KO mice beyond 4 months old ( Ermolova et al, 2011 ; Kramerova et al, 2016 ; Liu et al, 2020 ), we found that 2-month-old C3KO mice show similar performance in grip strength and resistance to fatigue tests compared to controls, suggesting that at this age C3KO are presymptomatic. Additionally, hyper-CKemia has been previously described in the early stages of the disease ( Urtasun et al, 1998 ; Fanin and Angelini 2015 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, it has been recently shown that calcium dyshomeostasis may be an early phenomenon in this model ( DiFranco et al, 2016 ). In contrast to reports from C3KO mice beyond 4 months old ( Ermolova et al, 2011 ; Kramerova et al, 2016 ; Liu et al, 2020 ), we found that 2-month-old C3KO mice show similar performance in grip strength and resistance to fatigue tests compared to controls, suggesting that at this age C3KO are presymptomatic. Additionally, hyper-CKemia has been previously described in the early stages of the disease ( Urtasun et al, 1998 ; Fanin and Angelini 2015 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The functional significance of these differentially expressed muscle genes were summarized in Table 6 . Decreased muscle expression of Csrp3, Fhl1, Myl2 and Tnnc1 and increased expression of Itpr1stimulate muscle regeneration and improve muscle function [ 26 , 27 , 30 , 31 , 32 , 33 , 34 , 38 ]. Decreased expression of Cyfip2 improves remodeling of extracellular matrix and leads to accelerated muscle regeneration [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAPN3 knockout studies have indicated that Ca 2+ /calmodulin-dependent protein kinase II (Ca-CaMKII)-mediated signal transduction is impaired ( 81 ), which not only decreases the slow muscle fiber phenotype and the fast muscle fiber phenotype ( 82 , 83 ), but also lowers the level of p38 MAPK activation. Eventually, the level of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC1α; a transcriptional co-regulator that coordinates muscle adaptive response) is decreased, leading to the decreased levels of transcription of genes involved in muscle adaptation ( 40 ).…”
Section: Capn3 In Diseasesmentioning
confidence: 99%